Day 1 Mon, May 02, 2016 2016
DOI: 10.4043/27294-ms
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Readiness Review of CFD-Based Numerical Wave Basin for Offshore Floater Design

Abstract: As Computational Fluid Dynamics (CFD) and High Performance Computing (HPC) technologies matured in many other industries, the offshore industry has begun to recognize CFD-based Numerical Wave Basin (NWB) as a design tool to evaluate offshore floater design more efficiently and with less uncertainty than the conventional ways relying on empirical methods. The recent NWB technology development has focused on the customization of CFD software for offshore design practices and validation of the developed analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Although CNWTs are more computationally costly than their lower fidelity counterparts, CNWT experiments can deliver accurate results in high resolution, which is particularly useful for the investigation of specific flow phenomena around coastal and offshore structures. Numerous studies are reported and reviewed in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], where CNWTs are employed for the analysis of different marine engineering problems.…”
Section: Computational Fluid Dynamics-based Numerical Wave Tanksmentioning
confidence: 99%
“…Although CNWTs are more computationally costly than their lower fidelity counterparts, CNWT experiments can deliver accurate results in high resolution, which is particularly useful for the investigation of specific flow phenomena around coastal and offshore structures. Numerous studies are reported and reviewed in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], where CNWTs are employed for the analysis of different marine engineering problems.…”
Section: Computational Fluid Dynamics-based Numerical Wave Tanksmentioning
confidence: 99%
“…Kim et al [19,20,21] have solved the problem of reflected waves without increasing the number of girds using Euler Overlay method(EOM). In this study, the Euler Overlay Method (EOM) was applied to simulate waves accurately without numerical damping in the 0.5L of inlet region.…”
Section: Numerical Setup and Calculation Conditionsmentioning
confidence: 99%
“…Mooring forces are handled via the interface to the 6-DOF ODE solver, either in terms of linear/torsional spring/damper system, or a direct interface to external mooring model software. Model performance and technical readiness of such a model for practical offshore floater design has been reported by Kim et al in [35].…”
Section: Mooring Systems Propulsion and Sailingmentioning
confidence: 99%